FUNGSI KOMISI PENGAWAS PERSAINGAN USAHA DAN LARANGAN PRAKTIK MONOPOLI - Berli Yudiansah (Faculty of Law, Universitas Lampung, 2020)
Nowadays, the law enforcement of prohibition monopolistic practices by KPPU is quite effective. But it is cannot be done optimally. This is influenced by the limited authority possessed by KPPU as regulated in Law No. Law. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition or the Antitrust Law, making it difficult to enforce the law. The problem in this paper is how the KPPU functions in law enforcement prohibiting monopolistic practices. The method used in this paper is a method with a normative and empirical juridical approachThe results of the research show that to maximize the KPPU's function in carrying out their duties, it is necessary to make improvements to the Antimonopoly Law, such as the loading of the KPPU's authority and duties to make it clearer. The establishment of special regulations for KPPU that are more technical in the context of applying the substance of the Antimonopoly Law.